2017
DOI: 10.1038/srep40166
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Coupling Distinguishes GJB1 Mutations Associated with CNS Manifestations of CMT1X from Those Without CNS Manifestations

Abstract: CMT1X, an X-linked inherited neuropathy, is caused by mutations in GJB1, which codes for Cx32, a gap junction protein expressed by Schwann cells and oligodendrocytes. Many GJB1 mutations cause central nervous system (CNS) abnormality in males, including stable subclinical signs and, less often, short-duration episodes characterized by motor difficulties and altered consciousness. However, some mutations have no apparent CNS effects. What distinguishes mutations with and without CNS manifestations has been uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 60 publications
(73 reference statements)
3
19
0
Order By: Relevance
“…This p.Trp132* variant has previously been reported in a Japanese male patient but no CNS involvement was documented . In recent research the GJB1 mutations were grouped into ‘peripheral nervous system only’ and mutations with CNS manifestations, and a distinct expression of gap junction plaques was revealed . But our findings argue that other underlying genetic or epigenetic factors might also contribute to the clinical diversity of CMTX1.…”
Section: Discussionsupporting
confidence: 45%
“…This p.Trp132* variant has previously been reported in a Japanese male patient but no CNS involvement was documented . In recent research the GJB1 mutations were grouped into ‘peripheral nervous system only’ and mutations with CNS manifestations, and a distinct expression of gap junction plaques was revealed . But our findings argue that other underlying genetic or epigenetic factors might also contribute to the clinical diversity of CMTX1.…”
Section: Discussionsupporting
confidence: 45%
“…Nevertheless, other studies have recently observed that even mutations associated with a complete loss of Cx32 can produce CNS dysfunction 41. Although a specific genotype-phenotype correlation between Cx32 mutation location (extracellular, intracellular or transmembrane) and WMLs has not been observed, recent studies suggest that the ability of Cx32 mutants to form gap junction plaques and produce adequate levels of junctional coupling in oligodendrocytes may relate to CNS manifestations 42. To all of the above, the occasional triggering of immune-mediated demyelination is also speculated to contribute to WMLs, as previously discussed 30…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, polymorphism in GJB1 are extremely rare, and a Although many other abnormalities in addition to peripheral neuropathy may be found in CMT, including central nervous system abnormalities, 14 spinal deformities, 15 and sensorineural deafness, [16][17][18] none of the patients included in this study had any of these manifestations. One patient (1.II-3) had neuropathic pain.…”
Section: Iii-2) Were Within Normal Values (Tables 1 and 2) It Is Verymentioning
confidence: 93%